A study on prevalence and factors associated to domestic violence by husband against married women of reproductive age (15-49) years of ward no 34 in Kathmandu Metropolitan City. - karki, Pramila (2012)
ABSTRACT: This study was undertaken as the partial fulfillment of requirement for the degree of bachelor in Public Health at Nepal Institute of Health Sciences. This study is conducted on "A study on prevalence and factors associated to Domestic Violence by husband against married women of reproductive age (15-49 yrs) of ward no 34 in Kathmandu Metropolitan City " as domestic violence is always taken as the family matter, not more concern is given to such issues and a need of carefully documented researches as such has not been documented adequately in Nepal till date. Gender-based violence is a serious issue that requires a comprehensive solution. Thus this study is an "eye opening". For the policy makers and program planners and will create some public and government attention in this 'over shadowed' public health problems as the nation. The objective of this study is to to assess the prevalence of domestic violence by husband against married women of reproductive age group (15-49 yrs) of Kathmandu Metropolitan City and to find the factors associated with it. Ward no 34 of Kathmandu Metropolitan City was taken as the study area purposively. For this quantitative, descriptive study, semi-structured questionnaire was used as a tool and face to face interview was the technique used for the purpose of collecting the data. Univariate and bivariate analysis was used to analyze the data. SPSS software was used for data entry and data analysis. The study reveals that among the total respondents, 49% were in the age group 25-35. Majority were of Brahmin/ Chetteri caste following Hinduism. 88% of the respondents were literate and 91% of respondents husband were literate. Among all the respondents, 78.04% have experienced any form of violence in their life time by husband among various types of violence data indicates that most have faced psychological/ emotional violence. Similarly, 67.07% of the victims of violence have not seek any kind of help from others. they have confined the problem of violence within themselves. Since, the prevalence of domestic violence by husband seems to be high, associated factors cannot be removed so implementation of proper laws and policies should be made, to discourage those factors. As well as female should be made capable and proper environment should be created so that women can raise voice against violence.